Ghrelin-Induced Alteration of Fatty Acid Profile in Adipose Tissue of Septic Rats - Yorulmaz, Hatice; Ozkok, Elif; Bulut, Yesim; Yilmaz, Okkes; Ates, Gulten; Tamer, Sule (Wiley, 2017)
[Abstract Not Available]